Acting to Let Someone Die - McGee, Andrew (Bioethics, 2015)
This paper examines the recent prominent view in medical ethics that withdrawing life-sustaining treatment (LST) is an act of killing. I trace this view to the rejection of the traditional claim that withdrawing LST is an omission rather than an act. Although that traditional claim is not as problematic as this recent prominent view suggests, my main claim is that even if we accepted that withdrawing LST should be classified as an act rather than as an omission, it could still be classified as letting die rather than killing. Even though omissions are contrasted with acts, letting die need not be, for one can let die by means of acts. The remainder of the paper is devoted to establishing this claim and addresses certain objections to it.